Advanced Raman Spectroscopy Using Nanofocusing of Light1 . Issue 8 (13th January 2017) - Nuytten, Thomas; Bogdanowicz, Janusz; Hantschel, Thomas; Schulze, Andreas; Favia, Paola; Bender, Hugo; De Wolf, Ingrid; Vandervorst, Wilfried
Abstract : Raman spectroscopy is uniquely sensitive to crucial material properties like stress and composition, but is inherently diffraction‐limited, impeding its application potential in nanostructured devices. Under correct polarization conditions, the Raman response from a periodic array of fins is dramatically enhanced inside the semiconductor material, re‐enabling fast and non‐destructive optical characterization of deep‐subwavelength semiconductor patterns. In this paper, it is shown that the effect is not limited to the material system where it was first observed, and results of nanofocused Raman spectroscopy in a variety of semiconductor materials are presented. The authors illustrate and discuss how the universality of the enhancement creates a unique potential for non‐invasive and rapid stress and composition measurements at the nanoscale. Abstract : The dramatic enhancement of Raman scattering intensities from periodic arrays of narrow semiconductor fins is reported. For a variety of materials, nanofocusing of the incident light translates Raman spectroscopy into the nanoscale world. This, in turn, enables optical stress and composition metrology on deep‐subwavelength semiconductor architectures.